P104 Prognostic factors in a large series of patients with stage II and III serous ovarian borderline tumors. (1st November 2019) - Maria, S; Farron, M; Maulard, A; Genestie, C; Pautier, P; Bentivegna, E; Leary, A; Chargari, C; Gouy, S; Morice, P
Abstract : Introduction/Background: The aim of this study was to assess prognostic factors in patients with stage II or III serous borderline ovarian tumors (SBOT) after a long term follow up in a large series. Methodology: Patients with SBOT and peritoneal implants treated or referred to our institution were retrospectively reviewed. All specimens (ovary and peritoneal implants) were reviewed by our expert pathologist. Results: Between 1971 and 2017, 212 patients were identified. Thirty-three (16%) patients had invasive implants. Sixty-eight patients underwent a conservative (fertility sparing) surgery. After a median follow up of 115 (range 12–512) months, 70 recurrences (33%) were observed (range 4–271 months), 28 (40%) of them under the form of invasive disease. Disease-free survival (DFS) at 5 and 10 years were 73% and 62% respectively. Invasive implants (vs non-invasive) (HR=5.37[1.29–22.26], p=0.013), and 3 or more peritoneal sites with implants (vs <3) (HR=3.56[1.11–11.39], p=0.024) were identified as predictors of recurrence in the form of invasive disease. But invasive implants were not associated with DFS (HR=1.39[0.77–2.51], p=0.27) nor with Overall Survival (OS) (HR=1.76[0.57–5.47], p=0.32). The presence of implants in more than 3 peritoneal sites was the only factor associated with both OS and DFS (p=0.049 and p=0.045). Conservative surgery was associated with DFS (HR=5.5[3.33–9.08], p<0.0001) but not with OS (HR=0.94[0.26–3.41], p=0.93). Others factors studied: stage (II vs III), residual disease after surgery, presence of micropapillary patterns, nodal surgery and the use of adjuvant treatment had no impact on OS or PFS. Conclusion: This study demonstrates that after a long term follow up, the types of peritoneal implants is no longer a prognostic factor on OS. Presence of implants on at least three peritoneal sites seems to impact significantly the risk of recurrence under the form of invasive disease and OS requiring then a specific follow-up in these patients. Disclosure: Nothing to disclose.